1982
DOI: 10.1111/j.1748-1716.1982.tb07102.x
|View full text |Cite
|
Sign up to set email alerts
|

Supersensitivity to substance P and physalaemin in rat salivary glands after denervation or decentralization

Abstract: Substance P, a putative neurotransmitter in mammals, and physalaemin, present in the skin of an amphibian, are both undecapeptides and belong to the family of tachykinins. The secretory effect of these tachykinins on parotid and submaxillary glands of the rat was examined. Dose-response curves showed that in the unoperated glands maximal secretory responses were obtained to an intravenous dose of 5-10 micrograms/kg of the tachykinins, that the amount of saliva secreted from the submaxillary gland was twice tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

1984
1984
1996
1996

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(26 citation statements)
references
References 30 publications
2
24
0
Order By: Relevance
“…1). This finding suggests supersensitivity of post-terminal SP receptors in the periphery following sciatic nerve lesion analogous to that previously reported after nerve section both centrally [8,9] and peripherally [10][11][12]. The small increase in smooth muscle reactivity could be due to the changes in the microenvironment of lesioned rats which rendered the smooth muscle more sensitive to direct electrical current.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…1). This finding suggests supersensitivity of post-terminal SP receptors in the periphery following sciatic nerve lesion analogous to that previously reported after nerve section both centrally [8,9] and peripherally [10][11][12]. The small increase in smooth muscle reactivity could be due to the changes in the microenvironment of lesioned rats which rendered the smooth muscle more sensitive to direct electrical current.…”
Section: Discussionsupporting
confidence: 67%
“…In another study in denervated rat parotid gland, it was shown that more cells respond to SP after denervation [11]. In addition studies on rat salivary glands showed that parasympathetic denervation of parotid gland can lead to development of a marked sensitisation to the tachykinins [12]. These results suggest that a supersensitivity like phenomenon may be produced after denervation of sensory nerves, but this has never been demonstrated in the skin.…”
Section: Introductionmentioning
confidence: 93%
“…These differences could reflect adaptation to the loss of the sympathetic innervation. The increased sensitivity of the secretory cells following sympathectomy (Ekstrom & Wahlestedt, 1982;Ekstrom, Mansson & Tobin, 1983) is probably the main cause of the larger NANC-induced secretory responses of sympathetically denervated glands to food intake previously recorded (Ekstrom et al 1993;Asztely et al 1994a), the decrease in the number of acinar granules and glandular amylase activity being, respectively, 50 versus 30% in intact glands. It is possible, however, that the larger percentage reductions in the contents of VIP and NPY in sympathetically denervated glands compared with those in the intact glands also contributed to the difference in magnitude of the effector responses.…”
Section: Discussionmentioning
confidence: 99%
“…VIP, substance P and NPY are secretagogues in the parotid gland of the rat. VIP, injected into the blood stream, elicits small volumes of saliva rich in protein (Ekstrom, Mdnsson & Tobin, 1983), whereas substance P produces a profuse flow of saliva with a low protein content (Ekstrom & Wahlestedt, 1982); in combination the two peptides are mutually potentiating (Ekstrom & Olgart, 1986). NPY, on the other hand, evokes only a tiny fluid response, if any, but releases amylase from the gland (Sharkey, Mathison, Sharif & Davison, 1989;Ekstrom et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In this gland, VIP is thought to act via cyclic AMP as intracellular messenger (Dehaye et al, 1985), but in contrast to 1-adrenoceptor stimulation the VIP activation of the gland cells also involves calcium (Christophe et al, 1989); parasympathomimetics and SP are also thought to act via the calcium pathway (Putney, 1986 There was no statistically significant increase in the weights of the contralateral parotid glands (supplied with an intact innervation) in response to the various drug infusions. Increased sensitivity to chemical stimuli, such as SP and VIP, of the secretory cells of the parotid glands subjected to parasympathetic denervation (Ekstrom, 1980;Ekstrom & Wahlestedt, 1982;Ekstrom et al, 1983b) or liquid diet (Ekstrom & Templeton, 1977) may have created favourable conditions for revealing trophic effects.…”
Section: Discussionmentioning
confidence: 99%